Cross-sectional study of obstetrics and gynecology-bound students in visiting rotations - Melody Y. Hou; Tiffany M. Hodgens; Mytien Nguyen; Marjorie J. Westervelt; Melissa A. Toland; Dowin Boatright; Claudia L. Lopez; Tonya L. Fancher (BMC Medical Education)
Abstract Background Recruitment of a more diverse obstetrics and gynecology workforce may help improve patient outcomes in the US, particularly among women of color. Visiting rotations play a role in competing for a position in an obstetrics and gynecology residency, however, not all students may be able to complete these expensive experiences. Our objective was to evaluate socioeconomic and other demographic differences among US obstetrics and gynecology-bound students who participate in visiting rotations versus those who do not. Methods We obtained de-identified data from the Association of American Medical Colleges for students graduating in US allopathic medical schools 2019 or 2020. We analyzed self-reported receipt of state and/or federal assistance to obtain postsecondary education, medical education debt, sex, and race and ethnicity data using chi-square and ANOVA analyses and logistic regression. Results Of 33,287 US graduating medical students, 1978 (5.9%) indicated “Obstetrics and Gynecology” as their intended practice and included socio-demographic data; 1110 (56.1%) of these completed at least one visiting rotation. In multivariable analysis controlling for medical education debt, race and ethnicity, and sex, students with moderate debt were less likely to complete any visiting rotation (aOR 0.68, 95% CI: 0.52, 0.89) and students with any debt were less likely to complete two or more visiting rotations than those without debt. However, Black students were significantly more likely to complete two or more rotations than white students when adjusted for debt and sex (aOR 1.48, 95% CI: 1.02, 2.11). Conclusions Among US obstetrics and gynecology-bound medical students, moderate medical education debt was associated with lower odds of completing visiting rotations when adjusted for race and ethnicity and sex. Black students were more likely to complete two or more visiting rotations compared to their white counterparts when adjusted for levels of debt, perhaps to improve the likelihood of a successful match that is lower than that of their white colleagues despite the risk of worsening their debt. Providing more financial support or deemphasizing the visiting rotation as part of the application could help recruit a workforce that better reflects the diversity of the general population.